Form destabilization: Between reality and projection - Mojsilovic, Mila (Arhitektura i urbanizam, 2024)
Moving from the concepts of project, space, and form wholeness problematizes the dematerialization of the world, allowing the production of architectural space as a place of new reality – between reality and its projection. Contemporary architectural openness enables the acceptance of diversity as the highest quality, in a zone where nothing is static or predefined. Shifting from symmetry towards complexity opens fields of world and object variability. This means that ambiguities evolve into the visibility of change. Their positioning on the same conceptual plane, between actual and potential reality, opens the possibility for multivalence. For architecture, this means that space is observed as a variety of movement intensities, where the mechanisms for form generation are established through digital media. The stratification of space in open fragmentation hides the logic of a system that, as an organizational principle, uses its opposite. In the plane of architectural production, the neutral framework of universal space for the production of diversity is translated into a digital one. A new definition of values and criteria, based on variability and potentiality, serves to introduce a metanarrative of multiplicity in terms of manifold ways of decoding the world and reality. What is confirmed is the capacity for the contemporaneity of architecture, in which the virtual appears as a post-digital formal state. The exploration of the openness and incompleteness of architecture is offered through the definition of a new stylistic key – as a new spatiotemporal and formal concept. What characterizes this temporal digital paradigm is the fragmentation of the homogeneous linear flow of time, which occurs by shifting mechanisms in favor of its new experience. The model is treated equally as a method that opens the alteration of the architectural form.
Keywords: virtual; destabilization; form; dematerialization; fragmentation